The Influence of Live-Streaming Shopping Activities on Attitude Toward Purchase Intention - Elsholiha, Hilwah Dibagiyya; Najib, Moh Farid; Amalia, Fatya Alty (Journal of Marketing Innovation (JMI), 2023)
The rapid development of marketing media, particularly live streaming services, is anticipated to be incorporated into the social, voice, and visual widespread in the future, which can influence customers' behavior while making purchasing decisions at any moment. The purpose of this paper is to determine the influence of live-streaming shopping activities on attitudes toward purchasing intentions. The purposeful ways to sample were implemented for this research, with questionnaires distributed digitally to TikTok social media users who had seen live-streaming promotions in Indonesia. The third version of SmartPLS was used to process the data collected from up to 443 respondents. The research results show each variable that significantly influences purchase intention includes credibility, informativeness, and interactivity through the intermediary, namely the variable attitude towards advertising. The researchers can use the data processing findings from the current research, which revealed customer attitudes toward advertising in the form of trust in sellers and trust in platforms, also to measure the influence of each variable interpreted as advertising value on consumer behavior, namely product purchase intention in TikTok live stream promotions.